Market And Media On The Digital Platform (Good and Bad Sides of Digitization) - Branković, Srbobran (Sociološki pregled, 2020)
The aim of the paper is to point out the good and bad sides of the changes that have occurred in the market and in the media with the occurrence of digitization. The analysis starts with the fact 1) that with digitization the market and the media are getting a powerful tool that gives many benefits in comparison with the pre-Internet age, but also with the fact 2) that this tool has its downside. Research shows that, on the same digital platform, millions of people often fall into addiction and, consequently, into depression. The most used method in the work was the analysis, especially sentiment analysis, as well as content analysis, and synthesis. Due to such strong and profound changes, it is necessary to analyze social trends and the consequences of those changes. It refers particularly to the addiction to social networks and media.